2002
DOI: 10.1034/j.1399-5448.2002.02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Aphidius colemani Vier. (Hymenoptera, Braconidae, Aphidiinae) detected in cereal fields in Germany

Abstract: Studies conducted in the 2000 cropping season at two different localities, Flaeming and Magdeburger Boerde in Germany, have provided new information on cereal aphid (Sitobion avenae (F.), Metopolophium dirhodum (Walker), and Rhopalosiphum padi (L.)) parasitoids in winter wheat; their species composition, relative abundance, hosts, and location effects. The average aphid population density was higher at Magdeburger Boerde and lower at Flaeming. Among the aphid species, Sitobion avenae was more abundant at Flaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 20 publications
3
29
0
Order By: Relevance
“…The parasitoid complex of cereal aphids in Serbia is similar to that found in the rest of Europe (Starý, 1976;Pankanin-Franczyk & Ceryngier, 1995;Adisu et al, 2002;Sigsgaard, 2002;Lumbierres et al, 2007) but the abundance of the individual species is different. Surprisingly, D. noxia is rarely recorded in Serbia (Petrović, 1996), and neighboring parts of Hungary, but it is more abundant in Central Europe (Hungary, Austria, Slovakia, Czech Republic, Poland, Germany), where it is the dominant pest of barley even at high altitudes (Starý, 2000;Starý et al, 2003).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The parasitoid complex of cereal aphids in Serbia is similar to that found in the rest of Europe (Starý, 1976;Pankanin-Franczyk & Ceryngier, 1995;Adisu et al, 2002;Sigsgaard, 2002;Lumbierres et al, 2007) but the abundance of the individual species is different. Surprisingly, D. noxia is rarely recorded in Serbia (Petrović, 1996), and neighboring parts of Hungary, but it is more abundant in Central Europe (Hungary, Austria, Slovakia, Czech Republic, Poland, Germany), where it is the dominant pest of barley even at high altitudes (Starý, 2000;Starý et al, 2003).…”
Section: Discussionsupporting
confidence: 68%
“…Also, P. gallicum and A. rhopalosiphi are dominant parasitoid species of M. dirhodum and R. padi. In western and central Europe P. gallicum is rarely collected (Starý, 1976, Adisu et al, 2002 but was recently found for the first time on the Iberian Peninsula (Lumbierres et al, 2007). Additionally, Toxares deltiger (Haliday) is unrecorded in Serbia, despite a long term survey of parasitoids there.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aphidophagous parasitoids, which are found in many regions of the world, help to regulate aphid populations in wheat crops (Adisu et al 2002, Schmidt et al 2003, Saethre et al 2011, Plećaša et al 2014, Elliot et al 2014, Zhao et al 2014. In temperate regions, is common aphids sexually reproduce during severe winters, and the female aphids usually lay their eggs on primary (harboreus) host plants (Starý and Havelka 2008).…”
mentioning
confidence: 99%